Pengaruh Pemberian Red Mud dan Bokasi Limbah Sayur Terhadap Pertumbuhan dan Hasil Selada Hijau pada Tanah Gambut - Demero, Alexander Frengky; Surachman, Surachman; Susana, Rini (JURNAL AGROPLASMA, 2024)
This research aims to find the best interaction dose of red mud and vegetable waste on the growth and yield of green lettuce plants on peat soil. This research used an experimental method with a Completely Randomized Factorial Design pattern consisting of two factors, each consisting of 3 treatment levels with 3 repetitions and consisting of 4 sample plants so that the total number of plants was 108 plants. The first factor, namely red mud (A) consists of a1 = 18 tonnes/ha equivalent to 220.5 g/plant, a2 = 20 tonnes/ha equivalent to 245 g/plant and a3 = 22 tonnes/ha equivalent to 269.5 g /plant and the second factor consists of b1 = 15 tonnes/ha equivalent to 184 g/plant, b2 = 20 tonnes/ha equivalent to 245 g/plant and b3 = 25 tonnes/ha equivalent to 306 g/plant. Observation variables include: Number of leaves, root volume, plant dry weight and plant fresh weight. Apart from the variables above, observations were also made of environmental conditions which included: soil pH, air temperature, relative humidity and daily rainfall. Based on the research results, it shows that giving 18 tons/ha of red mud is the best dose in increasing the fresh weight of plants and 20 tons/ha of vegetable waste fertilizer is the best dose in providing growth in the number of leaves in the 4th week of green lettuce plants on peat soil. Keywords: vegetable waste bokasi, red mud, green lettuce, peat soil